Electricity generation from EV body build with Al2O3 filler ER sandwiched by carbon fiber and lithium thin plate - Rahman, Mohammed Ataur; Raja, Ramiz; Rafia, Afroz; Hossain, Altab (Sila Science, 2015)

(untitled)
The environmental concerns and a shortage petroleum and limitation of battery capacity have driven efforts aimed at the bulk production of biodegradable material. This study proposes a new technology for electrical energy generation from EV body build with Al2O3 filler Epoxy Resin (ER) sandwiched by Carbon Fiber and Lithium thin plate. This technology has several advantages over the existing energy source of hybrid and electric vehicles. A developed small scale model car body would be able to produce energy 15% of 8.46 kWh battery pack, reduce 20% of traction power by decreasing 35% of total car weight and save 10% of energy consumption of air-conditioning system by providing heat insulation to the car roof. Therefore, the EVs/HEVs would be benefited by 45% in terms of energy efficient by newly developed body. Furthermore, the proposed body is very much friendly for the environment as it can be recyclable easily for the new product. Based on the overall benefit, the proposed car body has potentiality on the reduction of oil dependency and environmental emission. However, the main limiting factors are their thermal behavior and moderate ionic conductivity at low temperature. It is expected that the proposed car body with 8.46 kWh single charging battery pack would be able to travel 92 km.